METODE TILAWATI DALAM MENINGKATKAN KEMAMPUAN MEMBACA, MENULIS, DAN MENGHAFAL AL QUR’AN DI SD AL MADINA WONOSOBO - Zaid Mudhofar; Ngarifin Shidiq; Robingun Suyud (Ta'dib (Jurnal Ilmiah Pendidikan dan Peradaban Islam), 2021)
This research is based on the use of inappropriate methods in learning which can cause learning outcomes to be less than optimal. One of them is in learning the Qur'an. The tilawati method is a method that focuses on improving the ability to read, write, and memorize the Koran, the strategy used is to combine a classical approach and an individual approach with a reading and listening technique that uses songs (song rost). This study uses a qualitative approach. Then the method of interview, observation and documentation as the main method in data collection. Data analysis techniques using data reduction techniques, data presentation, and drawing conclusions. The results of the study stated that the first classical approach had been applied well and was able to help schools in improving students' reading, writing, and memorizing Al-Quran skills. Both individual approaches with reading listening techniques help teachers to find out in more detail the ability to read, write, and memorize the Al-Quran of each student because at the time of individual approach with reading techniques the teacher evaluates each student. The three inhibiting factors and supporting factors for the implementation of the tilawati method in improving the ability to read, write, and memorize the Al-Quran at SD Al Madina Wonosobo.